Driver's Liability for Negligence Resulting in Damage to Toll Facilities from the Maqasid Syariah Perspective (Case Study of the Medan-Tebing Tinggi-Kisaran Trans Sumatra Toll Road) - Damanik, Rahma Aulia; Hidayat, Rahmat (LEGAL BRIEF, 2025)
Along with the large volume of vehicles on toll roads, it has an impact on traffic accidents that are very detrimental to toll road users, both in the form of material losses and loss of life. On the other hand, toll road managers also experience losses in the form of damage to toll road facilities. This study aims to determine the regulations related to damage to toll facilities, as well as to determine the form of driver responsibility for damage to toll facilities. This problem is analyzed from the perspective of maqasid sharia on driver responsibility for negligence resulting in damage to toll facilities. The type of research is empirical legal research with a case approach (living case approach). The results of this study indicate that PP Number 15 of 2005 Concerning Toll Roads Article 86 paragraph 3 (a) (b) (c) and (d), is a regulation that regulates damage to toll facilities due to driver negligence. In the case of the Trans Sumatra Toll Road, damage to toll facilities caused by driver negligence is the responsibility of the driver, in accordance with the toll assets that were damaged. In the maqasid sharia perspective, driver responsibility is the application of the principle of Hif al-Mal (protecting property), therefore it is obligatory to maintain toll facilities.